(untitled) (Journal of Engineering, 2011)
single and binary competitive sorption of phenol and p-nitrophenol onto clay modified with quaternary ammonium (Hexadecyltrimethyl ammonium ) was investigated to obtain the adsorption isotherms constants for each solutes. The modified clay was prepared from blending of local bentonite with quaternary ammonium . The organoclay was characterized by cation exchange capacity. and surface area. The results show that paranitrophenol is being adsorbed faster than phenol . The experimental data for each solute was fitted well with the Freundlich isotherm model for single solute and with the combination of Freundlich- Langmuier model for binary system .